Obesity in inflammatory bowel disease: Gains in Adiposity despite high prevalence of Myopenia and Osteopenia - Bryant, RV; Schultz, CG; Ooi, S; Goess, C; Costello, SP; Vincent, AD; Schoeman, SN; Lim, A; Bartholomeusz, FD; Travis, SPL; Andrews, JM (MDPI, 2018)
Background: Rising rates of obesity have been reported in patients with inflammatory bowel disease (IBD); however, prospective data is lacking. The aim of this study is to prospectively evaluate body composition in adults with IBD over 24 months. Methods: Whole body dual energy X-ray absorptiometry (DXA) data was performed at 0 months, 12 months, and 24 months. Bone mineral density (BMD), fat mass index (FMI (kg)/height (m2)), appendicular skeletal muscle index (ASMI (kg)/height (m2)), visceral adipose tissue and the visceral adipose height index (VHI, VAT area (cm3)/height (m2)), and clinical and anthropometric assessments were performed at each time point. Multivariable linear mixed effects regression analyses were performed. Results: Initially, 154 participants were assessed at baseline (70% Crohn’s disease, 55% male, median age 31 years), of whom 129 underwent repeated DXA at 12 months, and 110 underwent repeated DXA at 24 months. Amongst those undergoing repeated DXA, their body mass index (BMI) significantly increased over time, such that by 24 months, 62% of patients were overweight or obese (annual change BMI β = 0.43, 95%CI = [0.18, 0.67], p = 0.0006). Gains in BMI related to increases in both FMI and VHI (β = 0.33, 95%CI = [0.14, 0.53], p = 0.0007; β = 0.08, 95%CI = [0.02, 0.13], p = 0.001; respectively), whereas ASMI decreased (β = −0.07, 95%CI = [−0.12, −0.01], p = 0.01) with a concordant rise in rates of myopenia (OR = 3.1 95%CI = [1.2, 7.7]; p = 0.01). Rates of osteopenia and osteoporosis were high (37%), but remained unchanged over time (p = 0.23). Conclusion: Increasing rates of obesity in patients with IBD coincide with decreases in lean muscle mass over time, while high rates of osteopenia remain stable. These previously undocumented issues warrant attention in routine care to prevent avoidable morbidity.